Complex and Nonlinear Dynamics in Electrical Power and Energy Storage Systems: Analysis, Modeling and Control - António M. Lopes; Penghua Li; Eduardo José Solteiro Pires; Liping Chen (Energies)
Energy demand has been increasing, and environmental concerns associated with energy consumption have emerged worldwide [...]